Changes in alcohol use associated with changes in HIV disease severity over time: A national longitudinal study in the Veterans Aging Cohort - Williams, Emily C. (Drug Alcohol Depend, 2018)
BACKGROUND: Among groups of persons living with HIV (PLWH), high-risk drinking trajectories are associated with HIV severity. Whether changes in individuals’ alcohol use are associated with changes in HIV severity over the same period is unknown. METHODS: Veterans Aging Cohort Study (VACS) data from VA’s EHR (2/1/2008–9/30/16) identified AUDITC screens for all PLWH. Pairs of AUDIT-C screens within 9–15 months were included if CD4 and/or viral load (VL) was measured within 9 months after baseline and follow-up AUDIT-Cs. Linear regression assessed change in HIV severity (CD4 and logVL) associated with AUDIT-C change adjusted for confounders. Mean changes in HIV severity were estimated for each AUDIT-C change value. For all measures of change, positive values indicate improvements (lower drinking and improved HIV severity). RESULTS: Among PLWH, 21,999 and 22,143 were eligible for CD4 and VL analyses, respectively. Most had non- or low-level drinking and stable consumption over time (mean AUDIT-C change=.08, SD=1.91). HIV severity improved over time [mean CD4 change=20.5 (SD 180.8); mean logVL change=0.12 (SD 0.71)]. AUDIT-C changes were associated non-linearly with changes in CD4 (p=0.03) and logVL (p<0.001). Improvement in HIV severity was greatest among those with stable AUDIT-C scores over time; those with greater AUDIT-C increases fared worse than those with smaller increases in or stable AUDIT-Cs. CONCLUSIONS: Improvement in HIV severity was greatest among PLWH with relatively stable drinking, most of whom initially did not drink or drank at low levels. Those with large changes (especially increases) in drinking appear at greatest risk for poor HIV control.